Landscape fire regime patterns in the Left-bank Forest-Steppe - Sydorenko , S. H. (Forestry and Forest Melioration, 2021)
Introduction Due to global warming and increasing aridity, the risk of increasing the frequency and scale of forest and other landscape fires remains high. One of the ways to reduce the fire risk is effective scientifically sound fire prevention treatment in the most vulnerable areas. The aim of the study was to assess preliminarily the spatial and temporal distribution of landscape fires in the predominant types of landscapes in the Left-Bank Forest-Steppe of Ukraine. Materials and Methods The main source of data was remote sensing satellite imagery. Thermal anomalies for the territory of the Left-Bank Forest-Steppe, detected by MODIS sensors during 2002–2016, have been revealed. The study analysed the flammability of the territory, taking into account all landscape fires: forest, agricultural, peat, pasture burning, etc. Data on FIRMS thermal anomalies with a fire probability of more than 30% were selected, and fires were analysed for each day of the period 2002–2020 during the fire season; normalized difference vegetation index (NDVI) was used. Results Spatial and temporal features of landscape fires during the fire season were determined. The total burnt area in the landscapes of the Left-Bank Forest-Steppe for the 15-year period (2006-2020) was estimated. Fire peaks have been identified for different types of landscapes. Tendencies towards increased fire hazards and density of fires in natural landscapes are revealed, depending on the current state of vegetation (passing of phenological phases by the main types of vegetation). The relationship between the average vegetation indices for the months during the fire season and the share of landscape fires was confirmed. The map of landscape fire frequency in the Left-Bank Forest-Steppe with a conditional allocation of wildfire risk zones was created. Conclusions According to the research results, the features and quantitative indicators of landscape fires in the Left-Bank Forest-Steppe of Ukraine were assessed. It is found that the area covered by fires in the natural ecosystems in the region can reach 810 thousand hectares during the fire season; the average area of fires per year is 350 thousand hectares. From 1,300 to 6,700 fires occur annually within the study region. Regularities of time distribution of fires and fire peaks have been described for each of the main types of landscapes. That information can be used to supplement the existing fire preparedness system due to the fire danger rate, which now in Ukraine does not take into account the phenological phases of the main vegetation in open landscapes. Geospatial raster layers of the landscape fire frequency for the Left Bank Forest-Steppe have been created with the identification of the most fire-hazardous areas that have a significant density of fires. These layers should be used in combination with vector layers of administrative districts, integrated territorial communities, and forestry enterprises to assess fire risks and identify the most vulnerable areas. Also, the developed maps can be used to implement a fire prevention system for specific, most dangerous areas. The results of the research are the basis for the development of methodological approaches to assessing the fire hazard of landscapes, which currently do not exist in Ukraine.